1. Раскроем скобки:
2p^3 − (p − 4 + 2p^3) = 2p^3 − p + 4 − 2p^3.
2. Применим правило вычитания подобных слагаемых (слагаемых, имеющих одинаковую буквенную часть):
2p^3 − p + 4 − 2p^3 = − p + 4.
Если p = 3, то − p + 4 = - 3 + 4 = 1.
ответ: при р = 3, 2p^3 − (p − 4 + 2p^3) = 1.
Объяснение:
вроде правильно
1. Раскроем скобки:
2p^3 − (p − 4 + 2p^3) = 2p^3 − p + 4 − 2p^3.
2. Применим правило вычитания подобных слагаемых (слагаемых, имеющих одинаковую буквенную часть):
2p^3 − p + 4 − 2p^3 = − p + 4.
Если p = 3, то − p + 4 = - 3 + 4 = 1.
ответ: при р = 3, 2p^3 − (p − 4 + 2p^3) = 1.
Объяснение:
вроде правильно